The Main Key To Implementation Of K3 In The Muhammadiyah Building Project Palangka Raya Kampus II During Pandemic - Manik, Herindo; Happy Puspasari, Veronika; Nuswantoro, Waluyo; Purwantoro, Almuntofa (Jurnal Civil Engineering Study, 2021)
Occupational safety is an important part of the implementation of construction projects, where occupational safety requires the same attention to quality, time and cost. Management must develop a safety work program and undertake to execute the program in order to create safety on the project site. Therefore, the identification of the primary key is required for the implementation of K3 during the pandemic. The research data was obtained through a survey of questionnaires distributed to the workers of the construction project of the Muhammadiyah Palangka Raya Campus II building and the analysis of the data was carried out in a descriptive way. Based on the results of the mean and standard deviation analysis, the results obtained are the dominant OSH factors during the pandemic in the Muhammadiyah Palangka Raya Campus II building construction project, namely (1) K3 Regulations and Procedures, (2) Employee participation, and (3) Employee communication.